2020
DOI: 10.3390/en13246734
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Strength Parameters of Cement Matrix with the Addition of Siliceous Fly Ash by Using Nanometric C-S-H Seeds

Abstract: Modification of a cement matrix using additives and admixtures has been a common practice for many years. The use of some mineral additives as substitutes for the cement, e.g., the siliceous fly ashes (FAs), has a positive effect on reducing the energy used in cement production. On the other hand, such activities may have negative effects due to the lowering of strength parameters of composites in early stages of curing. In order to solve this problem, over the last few years, thanks to the patented "seedings"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…After stabilizing the parameters of the apparatus, water was introduced into the cylinders so that the appropriate water/binder ratio of 0.3 was maintained. The total heat effect Q(t) was determined according to [58]…”
Section: Heat Of Hydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…After stabilizing the parameters of the apparatus, water was introduced into the cylinders so that the appropriate water/binder ratio of 0.3 was maintained. The total heat effect Q(t) was determined according to [58]…”
Section: Heat Of Hydrationmentioning
confidence: 99%
“…Preliminary studies presented in [50][51][52][53][54][55][56] confirmed the beneficial effect of this preparation on the mechanical parameters of concretes from the 28th day of their curing. The differences in the NA effect on the FA-modified composites and those made on pure Ordinary Portland Cement (OPC) were also compared [57][58][59][60]. In previous experiments it was also pointed out that NA with the active CSH phase seeds has a positive effect on improving the early age parameters of concretes and pastes containing FA, mainly by accelerating the initial reactions in the material microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is the C-S-H seeds. Since the addition of fly ash significantly retards the hydration process of the paste, the initial strength (within about 24 h) can be increased by adding C-S-H seeds [ 7 ]. The other is a superabsorbent polymer (SAP).…”
Section: Introductionmentioning
confidence: 99%
“…Fly ash and blast furnace slag are widely known admixture materials to replace cement [1][2][3], and some researchers used industrial wastes such as waste glass and steel slag to replace aggregates [4][5][6]. Recently, studies on materials that can improve the performance of cement composites by using small amounts are being conducted [7][8][9][10]. One of them is the C-S-H seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Another study [9] described that the use of high-modulus aggregate effectively resisted to the shrinkage development in concrete. A latest study by Szostak and Golewski [10] demonstrated that the use of a nanoadmixture containing nanometric C-S-H seeds can reduce drying shrinkage due to postponement of the beginning of matrix shrinkage via earlier intensification of exothermic reactions. It was also reported that external moisture supply via water ponding and/or fog misting during early hydration stages can also be a good option to mitigate the shrinkage cracking potential, but the reduced capillary porosity and early depercolation in low-w/b mixtures may result in limited curing effectiveness [11].…”
Section: Introductionmentioning
confidence: 99%